Integrating LLM-based agents with uncertainty-aware optimization for water-energy-carbon nexus management in irrigation districts - Lei Yu; Zhikai Li; Kai Huang; Fulin Li; Zixiang Lu; Yurui Fan; Yanan Jiang; Chenglong Zhang; Guangtao Fu (Water Research, 2027)

Advances in halide ion-mediated advanced oxidation processes for high-salinity wastewater treatment: Mechanisms of reactive oxidative species transformation and halogenated by-product formation - Yu Wang; Bing Yang; Yumin Zhang; Lingli Li; Chao Zhu; Yurui Li; Shaoqing Chen; Lili Ma; Mingyan Chen; Yucheng Liu (Chemical Engineering Journal, 2026)

Comparative genomics of parasitic and symbiotic microeukaryotes: Phylogenomic insights into lifestyle transitions and co-evolutionary dynamics - Yuexin Wang; Yihan Liu; Xiang Wang; Yurui Wang; Tengteng Zhang; Chen Shao (Molecular Phylogenetics and Evolution, 2026)

Seasonal hydrology shapes the spatiotemporal distribution of microplastics, antibiotics, ARGs, and sediment bacterial communities in the water-sediment interface - Yurui Zhang; Wei Wang; Xin Meng; Jingyan Hao; Jingru Yang; Simin Li (Journal of Environmental Chemical Engineering, 2026)

MoCN catalyst functionalized SnO₂-Sb/Ti anode enhanced electrochemical oxidation degradation of diclofenac: Performance, mechanism, and toxicity evolution - YuRui Yuan; Zihao Ye; Yuan Wu; Yan Zhang (Journal of Environmental Chemical Engineering, 2026)

A novel L-β-Galactoglucan alleviates physical fatigue by modulating load-specific metabolic pathways via the gut–muscle Axis - Jun He; Lingling Du; Meng Wang; Yurui Gou; Ziqi Xu; Shubin Yan; Yimiao Feng; Xiaohua Lyu; Jinyao Chen; Lishi Zhang; Xiaomeng Li (Food Research International, 2026)

Thermodynamically driven oxygen-rich vacancies in La2Ce2O7 boost Ni-catalyzed hydrogen production via steam reforming of plastic pyrolysis gas - Lin Li; Hwanyong Yang; Yurui Wang; Fuhua Xu; Shuang Li; Wei Zhang; Yixiang Shi; Ningsheng Cai (Chemical Engineering Journal, 2026)

Contrasting cold season temperature trends between eastern and western mid-latitude Eurasia over the past millennium - Yuan Yao; Yongsong Huang; Lu Wang; Yurui Zhang; Nan Dai; Liang Ning; Hanying Li; Jie Liang; Xiangzhong Li; Yanjun Cai; Hai Cheng (Quaternary Science Reviews, 2026)

Non-stationary framework of quantifying heat-driven drought propagation mechanisms in the Yellow River Basin of China - Ben Niu; Yi Li; Xingyun Qi; Maokai Song; Guiyuan Zhang; Yurui Fan; Zhi Li; Shie-Yui Liong (Journal of Hydrology, 2026)

A sustainable multifunctional packaging film incorporating L-glutamic acid and curcumin: Alleviating damage and enhancing fresh produce preservation - Liping Qiao; Mengyao Zhang; Junfu Liu; Junxi Li; Yuhan Liu; Yurui Wang; Laifeng Lu; Xia Liu (Food Bioscience, 2026)

LiDFOB/LiFSI/FEC-induced interphase regeneration and evaporative cooling of HFE in TMP-based electrolytes enable thermal runaway suppression of lithium metal batteries - Xiangming Hu; Hengyu Xu; Lihua Jiang; Yuan Cheng; Duxi Li; Duo Wang; Rong Fu; Shutong Jiang; Miaomiao Liu; Yurui Deng; Longfei Han; Mengdan Zhang (Chemical Engineering Journal, 2026)

Determining the sustainable brine extraction threshold in Qarhan Salt Lake via numerical simulation under multi-constraints - Han Jibin; Ma Hongkui; Han Wenhua; Ma Zhe; Huo Yurui; Zhang Luxi; Jiang Hongchen; Xiao Yong; Wang Jianping (Groundwater for Sustainable Development, 2026)

Multispectral analysis and molecular simulation of interaction mechanism between charged polysaccharides and myofibrillar protein in grass carp: Conformational dynamics and functional synergies - Jian Shi; Naiyong Xiao; Mingyu Yin; Jianrong Ma; Zhihui Liu; Yurui Zhang; Jianan Sun; Wenzheng Shi (Food Research International, 2026)

The role of phloretin in the thermal degradation of myofibrillar protein induced by myofibril-bound serine protease: Insights into structural and molecular mechanisms - Qianqian Liang; Xin Jiang; Yurui Zhang; Yan Li; Wenzheng Shi (Food Research International, 2026)

Changing characteristics of maize drought in different climate zones of China based on the continuous days without available precipitation - Yue Qi; Heling Wang; Yurui Tang; Yang Yang; Hong Zhao; Funian Zhao; Kai Zhang; Fei Chen; Xingxing Wei; Xiaofeng Yang (Theoretical and Applied Climatology, 2026)

Comprehensive phylogenomic analyses of ciliated protists with a revised classification of the phylum Ciliophora (Eukaryota, Alveolata) - Yurui Wang; Ying Yan; Zhenzhen Yi; Yan Zhao; Qianqian Zhang; Yong Chi; Tengyue Zhang; Weiwei Liu; Mingjian Liu; Borong Lu; Mingzhen Ma; Wenbao Zhuang; et al. (Science China Life Sciences, 2026)

VVFGO: a robust IMU/AHRS/USBL integrated navigation framework with adaptive virtual velocity factor correction for deep-sea docking - Ruiheng Liu; Xinyu Fei; Suohang Zhang; Yurui Zhang; Shipang Qian; Lu Wang; Yanhu Chen; Canjun Yang (Ocean Engineering, 2026)

Collaborative optimization of thermal safety and interphase stability of sodium-ion batteries based on ethoxy (pentafluoro) cyclotriphosphazene additive - Xiangming Hu; Shutong Jiang; Lihua Jiang; Yuan Cheng; Duo Wang; Hengyu Xu; Duxi Li; Yurui Deng; Longfei Han; Mengdan Zhang; Rong Fu; Miaomiao Liu (Journal of Cleaner Production, 2026)

Revealing the lifecycle evolution of hail-producing deep convective clouds by synergy of multi-source data - Qiang Li; Hongrong Shi; Yurui Xie; Rubin Jiang; Chaoying Wang; Yupeng Teng; Shuo Jia; Jianwei Wen; Disong Fu; Jiefan Yang; Xuehua Fan; Jinqiang Zhang; et al. (Atmospheric Research, 2026)

Relationship between lightning channel extension and charge transfer during initial continuous current and continuing current in negative artificially triggered lightning - Jingxuan Wang; Yang Zhang; Yijun Zhang; Yanfeng Fan; Yurui Li (Atmospheric Research, 2026)

Decolorization of Antarctic krill hydrolysate for salt reduction in surimi gel: improvement of taste, gel properties, and flavor profile - Yurui Zhang; Bo Wang; Yan Li; Xin Jiang; Shangkun Li; Keqiang Lai; Guoping Zhu; Wenzheng Shi (Food Research International, 2026)

Gobi-sourced dust and dust–climate feedbacks in the March 2023 East Asian storm - Shuna Liang; Bin Wang; Yurui Zhang; Junhua Yang; Ove W. Haugvaldstad; Hui Tang (Atmospheric Research, 2026)

China's rural revitalization in the context of rural depopulation: Challenges, opportunities and responses - Jingbo Yin; Jing Wang; Yurui Li; Yongjiang Zhang (Journal of Rural Studies, 2026)

Heat blocking mechanism and performance evaluation of flame-retardant modified bacterial cellulose aerogel for lithium-ion battery thermal runaway propagation prevention - Xiangming Hu; Zhijun Zhang; Yurui Deng; Zhiyuan Yang; Yajie Luo; Lihua Jiang; Mengdan Zhang; Longfei Han; Yuan Cheng (Chemical Engineering Journal, 2026)

Assessing Agricultural Production Greening Transformation and Exploring Sustainable Development Paths of China’s Loess Plateau - Lulu Qu; Yuhao Zhang; Yurui Li (Chinese Geographical Science, 2026)

Investigating the correlation between major taste substances and volatile flavor substances in Lateolabrax japonicus (sea bass) under bloodletting conditions - Meijiao Gui; Mengli Han; Zhenhao Song; Yurui Zhang; Dajun Wang; Shumin Zhang; Wenzheng Shi (Food Control, 2026)

Mechanistic insight into impacts of Cl− and Br− at high contents on phenol degradation and halogenated by-product formation in O3/H2O2 process - Bing Yang; Shijie Zhou; Xiangfu Huang; Qiang Zhou; Qinchuan Xu; Ying Qiu; Yurui Li; Mengnuo Wang; Yu Wang; Yuming Zhang; Mingyan Chen; Lili Ma; et al. (Process Safety and Environmental Protection, 2026)

Compound dry/wet and hot extremes decreased wheat/maize yield revealed by SHAP-RF and R-Vine Copula - Song Li; Yi Li; Guiyuan Zhang; Licheng Wang; Maokai Song; Yurui Fan; Kadambot H.M. Siddique (Field Crops Research, 2025)

Root trait responses of Ligustrum lucidum to edaphic stress across limestone and sandy shale areas - Yurui Cheng; Yongjun Jiang; Mengni Li; Jiabin Li; Fang Liu; Peiling Zhang; Qiufang He (Plant and Soil, 2025)

Current status of phylogenetic studies on ciliated protists (Alveolata, Protozoa, Ciliophora) by the OUC-group: advances, challenges and future perspectives - Feng Gao; Yang Bai; Yong Chi; Xiaochen Feng; Chunyu Lian; Borong Lu; Xiaotian Luo; Mingzhen Ma; Congcong Wang; Yurui Wang; Zhe Wang; Gongaote Zhang; et al. (Marine Life Science & Technology, 2025)
Ciliated protists (ciliates) represent a morphologically and genetically diverse group of single-celled eukaryotes, the phylogeny of which is critical for understanding eukaryotic evolution. Through international collaborations, the Laboratory of Protozoology at Ocean University of China (OUC-group) has conducted detailed research on ciliate phylogeny based on expanded taxonomic sampling, employing single gene as well as multi-gene markers, and phylogenomic datasets. We have systematically investigated > 1000 ciliate species spanning ~ 40 orders, sampled from diverse biotopes including marine environments in China seas and freshwater wetlands. This comprehensive sampling has generated three key datasets: (1) genomic DNA extracts from ~ 2600 strains, (2) ~ 2300 sequences of marker genes, and (3) single-cell genomic and/or transcriptomic datasets from ~ 120 species. Based on these datasets, the phylogenetic relationships covering all classes and most orders have been thoroughly reconstructed and investigated, resulting in the establishment of 93 new supraspecies taxa comprising two classes (Mesodiniea and Protocruziea), two subclasses (Protohypotrichia and Synhymenia), two orders (Wilbertomorphida and Lynnellida), 11 families, and 76 genera. Moreover, we have reconstructed a genome-scale tree of life for ciliates and provided an updated classification of the phylum Ciliophora. Furthermore, based on the robust phylogenetic tree of ciliates, we provide more reliable estimates for the origins and divergence times of the main ciliate groups. Future studies integrating advanced genomics, innovations in culturing and interdisciplinary applications will refine the ciliate tree of life, with broader impacts for our understanding of eukaryotic evolution and biodiversity.

Impacts of Qinling Mountains Elevation on Precipitation in Central China: A WRF Modelling Analysis - Bin Wang; Yiru Yang; Peter Clift; Wenting Gao; Li Xing; Yurui Zhang; Chris Brierley; Ting Sun; Hui Tang; Wei Shang; Ying Cheng; Shuangshuang Li; et al. (International Journal of Climatology, 2025)
The tectonically driven uplift of the Qinling Mountains during the Cenozoic may have resulted in significant climatic and environmental effects, but this remains poorly understood. This study investigates the influence of the Qinling Mountains' uplift on summer precipitation patterns in central China using the Weather Research and Forecasting (WRF) model to design topographic sensitivity experiments. The results show that the uplift of the Qinling Mountains leads to the intensification of the spatial distribution of precipitation in China, with increased precipitation in the south and decreased precipitation in the north. The uplift of the Qinling Mountains from an average elevation of 400 m to their current elevation results in a 13% (64.3 mm) decrease in precipitation north of the Qinling Mountains, a 39% (134.4 mm) increase in the Qinling Mountains, and a 1.5% (8.1 mm) increase to the south. In particular, precipitation in the Loess Plateau decreased by 62.7 mm (18%). As the Qinling Mountains uplift, the physical barrier effect is enhanced, leading to a reduction in water vapour over the Qinling Mountains. However, the forced uplift of air masses results in enhanced vertical motion, which in turn increases summer precipitation over the Qinling Mountains. In contrast, although water vapour accumulation occurs to the north of the Qinling Mountains, the absence of topographic forcing leads to decreased precipitation. When the Qinling Mountains uplifted to an average elevation of 1600 m, they began to exert a more pronounced blocking effect on wind and water vapour transport. This elevation effectively transformed the Qinling Mountains into a natural barrier, further separating the climatic regimes of the north and south of China. These findings indicate that the changes in elevation during the uplift of the Qinling Mountains have had a marked impact on the spatial distribution of precipitation in the central China.

A vertical docking system based on the autonomous underwater shuttle for seafloor communication relay - Xiaoyan Zhao; Xinyu Fei; Suohang Zhang; Ning Tan; Zhangpeng Tu; Anzhe Yi; Yurui Zhang; Canjun Yang; Yanhu Chen (Ocean Engineering, 2025)

Betaine-based natural deep eutectic solvents (NADESs) for enhanced cryoprotection: Insights into hydrogen bonding behavior and antifreeze mechanisms - Yan Li; Qianqian Liang; Xin Jiang; Yurui Zhang; Wenzheng Shi (Food Chemistry, 2025)

Effects of extreme heat on vegetation carbon sequestration in the Yellow River Basin - Guanpeng Dong; Yuchen Guo; Hongjuan Zhang; Yansui Liu; Yurui Li; Han Zhang; Junting Zhong (Science China Earth Sciences, 2025)

Temperature shapes the global distribution of organic carbon in lake surface sediments - Yongquan Lin; Sheng Yang; Mengting Zhao; Xuerui Lyu; Lingmei Xu; Wengang Kang; Xinwei Yan; Yurui Zhang; Jianbao Liu (Journal of Geographical Sciences, 2025)

Genotoxicity mode of action exploration of polyethylene glycol terephthalate (PET) acetic acid migration solution under repeated-dose exposure in rats - Liang Wang; Li Cao; Xiaoya Wang; Yufei Liu; Weiwei Zhang; Yurui Gou; Jun He; Jiao Huo; Xiaomeng Li; Jinyao Chen (Mutation Research - Genetic Toxicology and Environmental Mutagenesis, 2025)

Climate and land use regulate vegetation–runoff interaction pathways in the three-river source region - Guiyuan Zhang; Darrell Tang; Song Li; Yurui Fan; Alim Pulatov; Aili Sun; Xingyun Qi; Licheng Wang; Yi Li (Journal of Environmental Management, 2025)

A 5-year field study to assess interannual variability and determinants of cotton fiber quality in intercropping systems - Haoyue Qin; Yurui Tang; Xin Li; Yurong Qiu; Jian Wang; Yingchun Han; Guoping Wang; Shiwu Xiong; Minghua Xin; Wenli Du; Lu Feng; Yongjiang Zhang; et al. (European Journal of Agronomy, 2025)

B-Mg co-substituted binder-free ZSM-5 zeolites with recrystallized cheese-like hierarchical porosity for enhanced benzene-methanol alkylation: Synergistic micro-meso-macroporous mass transfer and acid-site engineering - Run Cai; Likun Wen; Yihua Cao; Yindan Wu; Yichen Song; Xinyu Wang; Hanyang Zhou; Yurui Zhang; Xiaoping Dai; Xin Zhang (Chemical Engineering Journal, 2025)

Stable photosynthetic characteristics are associated with aphid resistance in sorghum - Yutao Shao; Peng Zhang; Le Hao; Yurui Zhang; Jialing Li; Zhenjie Wang (Theoretical and Experimental Plant Physiology, 2025)

Transparent wood electrode for electrocatalysis: Preparation, micro/nano structures fabrication, functionalization and applications - Yurui Huang; Xianze Zhang; Linxiang Li; Ruichen Lu; Xueqiang Zhang (Chemical Engineering Journal, 2025)

Manganese in drinking water distribution systems: A comprehensive review on the occurrence, migration transformation mechanisms, and control strategies - Yuan Wu; Yan Jia; Zhihui Hu; Yurui Yuan; Yan Zhang (Critical Reviews in Environmental Science and Technology, 2025)

Paris saponin VII restrains PD-L1 mediated immune evasion through the AKT1 and STAT3 signaling pathways - Yudi Wang; Yanli Li; Yurui Zhang; Yitong Li; Leilei Zhao; Lanxin Tong; Xiao Zhu; Jianyong Wang; Yucui Dong (Chemico-Biological Interactions, 2025)

Succulent and no-succulent plants in desert grassland ecosystems differ in their leaf traits - Yurui Zhang; Lijuan Chen; Feifei Dong; Ziyue Li; Zhi Zheng (Plant and Soil, 2025)

Improved semi-infinite interval type-2 fuzzy multi-objective programming with integrated multi-criteria decision analysis for sustainable water resource management - Xi Zhang; Lei Jin; Yurui Fan; Li Wang; Jing Liu; Pangpang Gao (Journal of Water Process Engineering, 2025)

GepA, a GGDEF-EAL protein, regulates biofilm formation and swimming motility in Vibrio parahaemolyticus - Miaomiao Zhang; Yurui Zhu; Xue Li; Xi Luo; Hui Sun; Shuhui Xiong; Renfei Lu; Yiquan Zhang (Archives of Microbiology, 2025)

Linkage between leaf anatomical structure and key leaf economic traits across co-existing species in temperate forests - Zhi Zheng; Yurui Zhang; Feifei Dong; Lijuan Chen; Ziyue Li (Plant and Soil, 2025)

The clinical characteristics of Streptococcus equi ssp. zooepidemicus causing acute death in pigs and its prevention with chimeric monoclonal antibodies - Chen Yuan; Yuchang Wang; Xiaowen Zhang; Xingyu Tian; Ying Liang; Fei Pan; Haoshuai Song; Linya Xia; Zhihui Wu; Wenqing Wang; Xiaowen Zhang; Yurui Xie; et al. (Veterinary Microbiology, 2025)

Poleward expansion of North Pacific gyre circulation during the warm early Eocene inferred from inter-model comparisons - Yurui Zhang; Agatha M. de Boer; Guojin Qin; Daniel J. Lunt; David K. Hutchinson; Sebastian Steinig; Igor Niezgodzki; Bridget S. Wade; Xiaoqing Liu; Christopher J. Poulsen; Gerrit Lohmann (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Exploring key aroma differences of three Fenghuang Dancong oolong teas and their perception interactions with caffeine via sensomics approach - Yurui Song; Jingzhe Li; Qiayun Ding; Xiang Yang; Jieyao Yu; Yanyan Zhang; Yijun Wang; Xiaochun Wan; Xiaoting Zhai (Food Research International, 2025)

Multidimensional deconstruction and workable solutions for addressing China's food security issues: From the perspective of sustainable diets - Xiaohua Zhu; Yan Zhang; Yuanyuan Zhu; Yurui Li; Jiaxing Cui; Bohua Yu (Land Use Policy, 2025)

Analyzing water resources with sector characteristics in Fujian Province utilizing S2-DR-BIMCCP model integrated with the Gini coefficient - Ruolin Bai; Lei Jin; Yurui Fan; Xi Zhang; Ruoyu Yin; Yi Wei (Journal of Cleaner Production, 2025)

A flexible, highly sensitive, and anti-strain interference sensing fabric based on conjugated electrospinning core–shell conductive nanofiber yarns for ultra-stable pressure sensing and human–machine interaction - Wenqi Wu; Xu Jin; Adilaimu Tiliman; Fan Zhang; Ge Bai; Yurui He; Gaoling Jin; Bin Wang; Xiuqin Zhang; Rui Wang (Chemical Engineering Journal, 2025)

Relations between root anatomical traits and leaf resource-use efficiency in alpine meadows of the Tibetan Plateau - Zhi Zheng; Cong Wang; Yurui Zhang (Plant and Soil, 2025)

Extraction optimisation and compositional characterisation of total flavonoids from the Chinese herb tulip: a natural source of antioxidants and anti-inflammatory agents - Jiafeng Ye; Jiamin Cao; Xian Chen; Jingjing Ma; Yangchen Li; Xia Gao; Yurui Zhang; Chunli Wang (Natural Product Research, 2024)

Multidimensional effects of green waste vermicomposting on cadmium contaminated soil ecosystems: From physicochemical properties to microbial communities - Li Huang; Yurui Meng; Boyou Pan; Bogui Pan; Junyu Wei; Jinhua Ding; Yingfeng Deng; Xianglan Su; Ziwei Yuan; Menghao Zhang (Journal of Hazardous Materials, 2024)

Thermal stability of PVDF-HFP based gel electrolyte for high performance and safe lithium metal batteries - Xiaoxuan Wei; Yurui Deng; Xiangming Hu; Zhiyuan Yang; Guoyu Han; Hengxu Xu; Zhijun Zhang (Chemical Engineering Journal, 2024)

Comparison of non-volatile compounds of Penaeus vannemei with different drying treatments via multidimensional infrared spectroscopy - Jian Shi; Naiyong Xiao; Mingyu Yin; Jianrong Ma; Yurui Zhang; Qianqian Liang; Xin Jiang; Yan Li; Wenzheng Shi (Food Chemistry, 2024)

CuFeS2/GAC particle combined with electrochemical activation of persulfates for efficient degradation of carbamazepine - YuRui Yuan; Xincheng Ye; Yan Jia; Yuan Wu; Yan Zhang (Chemosphere, 2024)

Morphology, morphogenesis and molecular phylogeny of a new soil ciliate, Lamtostyla paravitiphila nov. spec. (Ciliophora, Hypotrichia) - Tengteng Zhang; Furui Lu; Xiaoqing Yang; Yurui Wang; Chen Shao (European Journal of Protistology, 2024)

Orbital modulation of an intensified hydrological cycle during the Paleocene-Eocene Thermal Maximum - Jingyu Zhang; Chunlian Wang; Xiaohua Teng; David B. Kemp; Zhixiang Wang; Hu Yang; Congcong Gai; Yurui Zhang; Yi Zhong; Xiaodong Jiang; Qi Zhang; Weijie Zhang; et al. (Earth and Planetary Science Letters, 2024)

Increased overyielding probability and yield stability from a 5-year cotton-based intercropping - Yurui Tang; Yurong Qiu; Xin Li; Haoyue Qin; Jian Wang; Shijie Zhang; Yingchun Han; Lu Feng; Guoping Wang; Beifang Yang; Yaping Lei; Shiwu Xiong; et al. (European Journal of Agronomy, 2024)

Effects of exogenous steroid hormones on growth, body color, and gonadal development in the Opsariichthys bidens - Qingyuan Liu; Jinchun Hu; Yurui Lin; Xinrui Wu; Yujun Feng; Jiazheng Ye; Kai Zhang; Shanjian Zheng (Fish Physiology and Biochemistry, 2024)

The shift to plant-based dietary patterns in China would have significant effects on cultivated land resources - Xiaohua Zhu; Yan Zhang; Yuanyuan Zhu; Yurui Li (Science Bulletin, 2024)

Environmental responsibility, emotion and public water-saving behavior - Xingle Long; Yurui Liu; Wensi Cheng; Jinyu Zhang; Chuanmin Jin; Si’an Tao (Environment, Development and Sustainability, 2023)

Three closely-related subclasses Phacodiniidia Small & Lynn, 1985, Protohypotrichia Shi et al., 1999, and Euplotia Jankowski, 1979 (Protista, Ciliophora): A new contribution to their phylogeny with reconsiderations on the evolutionary hypotheses - Chunyu Lian; Yan Zhao; Ping Li; Tengteng Zhang; Khaled A.S. Al-Rasheid; Naomi A. Stover; Yurui Wang; Chen Shao (Molecular Phylogenetics and Evolution, 2023)

Directly linking plant N, P and K nutrition to biomass production in cotton-based intercropping systems - Yurong Qiu; Xin Li; Yurui Tang; Shiwu Xiong; Yingchun Han; Zhanbiao Wang; Lu Feng; Guoping Wang; Beifang Yang; Yaping Lei; Wenli Du; Xiaoyu Zhi; et al. (European Journal of Agronomy, 2023)

The postulation of intermittent land bridges as an explanation for reiterated colonization events of Madagascar by African vertebrates: An in-depth review and novel insights in honour of the late Judith Masters and Fabien Génin - Daniel Aslanian; Romain Pellen; Marina Rabineau; Maryline Moulin; Estelle Leroux; Antoine Delaunay; Guillaume Baby; Simon Courgeon; Bastien Linol; Jean-Pierre Suc; Speranta Popescu; Séverine Fauquette; et al. (Earth-Science Reviews, 2023)

Belowground facilitation of plant mixtures on rhizosphere soil of Commelina communis grown on extremely Cu- and Cd-contaminated mine: From soil quality to bacterial community - Tan Ke; Huan Wang; Shaofeng Li; Yurui Zhang; Panpan Wang; Chaoqi Chen; Lu Lu; Lanzhou Chen (Applied Soil Ecology, 2023)

Regularity of rural settlement changes driven by rapid urbanization in North China over the three decades - Yansui Liu; Cong Ou; Yurui Li; Liqiang Zhang; Jianhua He (Science Bulletin, 2023)

Semi-urbanization identity formation through role creation theory: The dynamic villagers’ perspectives - Wang Qianyi; Li Yurui; Zhang Xuanchang; Ren Yu (Applied Geography, 2023)

Distinguishing anaerobic digestion from electrochemical anaerobic digestion: Metabolic pathways and the role of the microbial community - Nan Wang; Yutong Yang; Kunde Xu; Xiangang Long; Yurui Zhang; Hongzhou Liu; Tiezhu Chen; Jianchang Li (Chemosphere, 2023)

Comparative genome analysis of three euplotid protists provides insights into the evolution of nanochromosomes in unicellular eukaryotic organisms - Didi Jin; Chao Li; Xiao Chen; Adam Byerly; Naomi A. Stover; Tengteng Zhang; Chen Shao; Yurui Wang (Marine Life Science & Technology, 2023)
One of the most diverse clades of ciliated protozoa, the class Spirotrichea, displays a series of unique characters in terms of eukaryotic macronuclear (MAC) genome, including high fragmentation that produces nanochromosomes. However, the genomic diversity and evolution of nanochromosomes and gene families for spirotrich MAC genomes are poorly understood. In this study, we assemble the MAC genome of a representative euplotid (a new model organism in Spirotrichea) species, Euplotes aediculatus . Our results indicate that: (a) the MAC genome includes 35,465 contigs with a total length of 97.3 Mb and a contig N50 of 3.4 kb, and contains 13,145 complete nanochromosomes and 43,194 predicted genes, with the majority of these nanochromosomes containing tiny introns and harboring only one gene; (b) genomic comparisons between E. aediculatus and other reported spirotrichs indicate that average GC content and genome fragmentation levels exhibit interspecific variation, and chromosome breaking sites (CBSs) might be lost during evolution, resulting in the increase of multi-gene nanochromosome; (c) gene families associated with chitin metabolism and FoxO signaling pathway are expanded in E. aediculatus , suggesting their potential roles in environment adaptation and survival strategies of E. aediculatus ; and (d) a programmed ribosomal frameshift (PRF) with a conservative motif 5′-AAATAR-3′ tends to occur in longer genes with more exons, and PRF genes play an important role in many cellular regulation processes.

Design and testing of a mechanized brush-screen cooperative vibration harvester for mudflat-buried shellfish based on the discrete element method - Hangqi Li; Gang Mu; Hanbing Zhang; Hao Wu; Fawei Liu; Zhenyin Sun; Qian Zhang; Yizhou Wang; Yurui Wang; Xiuchen Li; Guochen Zhang (Frontiers in Marine Science, 2023)
Introduction To enhance the application of mechanized harvesting and supplement research on harvesting theory in mudflat-buried shellfish harvesting in China, a brush-screen cooperative mudflat-buried shellfish vibration harvester was designed. Methods The harvester is primarily composed of a crank rocker double-layer vibrating screen, two stage rolling brush, and a conveyor chain. White clams ( Mactra veneriformis ) cultured in mudflats were used as the research objects in this paper, and the mechanics and motion states of the shellfish on the vibrating screen were analyzed. The shellfish harvesting simulation response surface experiments based on the discrete element method (DEM) were conducted to analyze the influence of the main operating parameters on the quantity of shellfish harvested. Results The results revealed that the number of shellfish harvested was significantly influenced ( p < 0.01) by vibrating screen amplitude, first-stage spiral rolling stainless steel brush rotation rate, and harvester travel speed. The optimal combination of key parameters was 1.4 mm, 40 rpm, and 10 m/min, respectively. With these values, the projected shellfish crushing rate was 2.82% and the shellfish harvesting efficiency was 125 pieces/m 2 . The equipment was then manufactured and the shellfish harvesting verification test was performed under the same operating parameters as the simulation. Test results indicated that the harvesting efficiency of the equipment was 114 pieces/m 2 and the shellfish crushing rate was 6.97%. Discussion The shellfish harvesting work could be completed by the equipment effectively and with low loss. The results of this study provide a theoretical reference for a novel mechanized method of harvesting mudflat-buried shellfish.

Occupant-centric dynamic heating and cooling loads simplified prediction model for urban community at energy planning stage - Shuqin Chen; Yurui Huang; Xiyong Zhang; Frédéric Kuznik; Xi He; Yuhang Ma; Yuxuan Cai (Sustainable Cities and Society, 2023)

Unraveling the microbial succession during the natural fermentation of grass carp and their correlation with volatile flavor formation - Naiyong Xiao; Huiya Xu; Yun Hu; Yurui Zhang; Quanyou Guo; Wenzheng Shi (Food Research International, 2023)

Research on non-contact wet mateable connector for optical communication and power transmission - Zhiyong Duan; Yurui Zhang; Jiaqi Hu; Bohao He; Canjun Yang (Frontiers in Marine Science, 2023)
At present, contact watertight connectors are commonly utilized for the connection between underwater electromechanical equipment and the seabed observation network. Such traditional watertight connectors are easy to be irreversibly worn when plugging and unplugging, however, they have complicated sealing structures and limited service life. This paper designs a Non-contact Wet Mateable connector for Optical Communication and Power Transmission (OCPT-NWMC), which is based on technology of Contactless Power Transmission (CLPT) and optical communication. Docking structure of the sockets and plugs are designed, facilitating Remotely Operated Vehicle (ROV) to operate. A prototype of the OCPT-NWMC was established. The experimental results show that the connector designed can achieve 200W power transmission, with a maximum power transmission efficiency of 94%. The communication bandwidth reaches 18MHz. The OCPT-NWMC can assist the rapid and safe deployment and operation of seabed observation network.

Projections of future precipitation and air temperature over the Tibetan Plateau based on Coupled Model Intercomparison Project Phase 6 multimodel ensembles - Wenqing Zhang; Liu Liu; Yurui Lun; Lei Cheng; Xiuping Li; Zongxue Xu (International Journal of Climatology, 2022)
In the context of global warming and the release of projection results from the Coupled Model Intercomparison Project Phase 6 (CMIP6), it is important to conduct research on climate change on the Tibetan Plateau (TP) which exhibits unique geographic characteristics and complex climatic conditions. Using 10 general circulation models (GCMs) from CMIP6 corrected for bias by the daily translation (DT) method, we investigated the projected changes in precipitation and air temperature for the mid‐term (2031–2050) and long‐term (2061–2080) of the 21st century on the TP after evaluating the reliability of the bias correction, for four scenarios based on different combinations of shared socioeconomic pathways and representative concentration pathways. The multimodel ensembles (MMEs) indicated that the projected annual precipitation shows an increasing trend for the mid‐term and long‐term periods, with the projected increase for the long‐term primarily concentrated in areas with less precipitation. Meanwhile, the future precipitation changes exhibit a significant elevation dependency. The rate of increase of precipitation firstly fluctuates and then gradually increases along with the elevation increasing from 1,500 to 5,800 m. The valley value of rate mainly appears in two elevation zones (2,200–2,600 m and 3,400–3,800 m). The projected temporal changes in annual air temperatures reveal obvious warming over the TP. The projected warming is overall more pronounced with increase in elevation; however, it reaches a peak at approximately 5,000–5,200 m and then slows down slightly, indicating that warming is not dependent on elevation in the higher elevation zones. The present results have important implications for investigating the impacts of climate change on the water cycle in alpine regions.

Research on COD Soft Measurement Technology Based on Multi-Parameter Coupling Analysis Method - Yurui Zhang; Zhiyong Duan; Anzhe Yi; Jiaqi Hu; Yanhu Chen (Journal of Marine Science and Engineering, 2022)
This paper presents a soft measurement technique for COD (Chemical Oxygen Demand) based on the multiparameter coupling analysis method. First, through mechanism analysis and correlation analysis of historical data during the measurement process, water quality parameters, such as hydrogen potential (PH), dissolved oxygen (DO), turbidity (TU), and electrical conductivity (EC), can be used to estimate COD values. To further improve the estimation accuracy of the water quality parameter model, we adopted a modeling method combining a BP neural network and support vector machine, which showed an average relative error of 6.13% and an absolute coefficient of up to 0.9605. Finally, experiments in a lake environment demonstrate that this method shows excellent performance, with highly reliable and accurate prediction results.

Whole Genomic DNA Methylation Profiling of CpG Sites in Promoter Regions of Dorsal Root Ganglion in Diabetic Neuropathic Pain Mice - Wen Chen; Ting Lan; Qingyu Sun; Yurui Zhang; Danmin Shen; Tingting Hu; Jing Liu; Yingzi Chong; Peipei Wang; Qian Li; Weihua Cui; Fei Yang (Journal of Molecular Neuroscience, 2021)

Biogeographic mechanisms involved in the colonization of Madagascar by African vertebrates: Rifting, rafting and runways - Judith C. Masters; Fabien Génin; Yurui Zhang; Romain Pellen; Thierry Huck; Paul P. A. Mazza; Marina Rabineau; Moctar Doucouré; Daniel Aslanian (Journal of Biogeography, 2021)
Aim For 80 years, popular opinion has held that most of Madagascar's terrestrial vertebrates arrived from Africa by transoceanic dispersal (i.e. rafting or swimming). We reviewed this proposition, focussing on three ad hoc hypotheses proposed to render this unlikely scenario more feasible: (a) Could hibernation have helped mammals to reach Madagascar? (b) Could the aquatic abilities of hippopotamuses have enabled them to swim the Mozambique Channel? (c) How valid is the Ali‐Huber model predicting that eastward Palaeogene surface currents allowed rafts to reach Madagascar in 3–4 weeks? Finally, we explored the alternative hypothesis of geodispersal via short‐lived land bridges between Africa and Madagascar. Location East Africa, Madagascar, Mozambique Channel. Taxa Fish, amphibians, reptiles, birds, mammals. Methods We established colonization timeframes using molecular divergence dates estimated for Malagasy vertebrate lineages. We reviewed the likelihood of the “torpid waif” and “swimming hippopotamus” hypotheses, and re‐investigated Ali and Huber's model of Eocene jet‐like currents by tracking particle trajectories in currents simulated using the Institut Pierre‐Simon Laplace Earth System Model. Finally, we summarized recent geological findings from the Mozambique Channel, and used them to compile palaeosedimentological maps using PLACA4D. Results Madagascar's vertebrate fauna has complex origins. Hibernation is probably an adaptation to Madagascar's hypervariable climate, rather than a facilitator of mammal dispersal. Hippopotamus physiology precludes the ability to cross an oceanic channel deeper than 4 m and hundreds of km wide. The Ali‐Huber model of Palaeogene currents considerably underestimated the time required to cross the Mozambique Channel under simulated palaeogeographic conditions. New geological data indicate the existence of three short‐lived land bridges between Africa and Madagascar at 66–60 Ma, 36–30 Ma and 12–05 Ma. Main conclusion The three Cenozoic land bridges afford a more grounded hypothesis for the dispersal of Madagascar's extant biota than transoceanic rafting or swimming, although vicariance, island hopping and limited rafting also played a role.

Systematics and Multi-Gene Phylogeny of the Subfamily Nothoholostichinae (Ciliophora, Hypotrichia), With Integrative Description of a New Marine Species Nothoholosticha luporinii n. sp. - Tengyue Zhang; Yurui Wang; Ting Cheng; Jiyang Ma; Peter Vd’ačný; Weibo Song; Chen Shao (Frontiers in Marine Science, 2020)
Morphogenesis of ciliated protists attracts a lot of attention, because their huge morphological diversity is related to formation of ciliary structures during cell division. In the present work, the morphology and morphogenesis as well as the phylogenetic position of a new, marine hypotrich ciliate, Nothoholosticha luporinii n. sp., were investigated. The new species is characterized by having a combination of the following features: a bicorona whose anterior row contains four frontal cirri and posterior row includes only two cirri, a single buccal cirrus, midventral complex composed of about 30 cirral pairs, one pretransverse cirrus, 3–6 transverse cirri, one left and one right marginal cirral row; three bipolar dorsal kineties; contractile vacuole located in about 2/3 of the body length, two types of cortical granules, and many macronuclear nodules scattered throughout the cytoplasm. The morphogenesis of N. luporinii follows the ontogenetic mode of Pseudokeronopsis , a well-known and closely related genus except that the macronucleus fuses into a single mass in the middle fission stage. Phylogenetic analyses based on the rDNA operon classify Nothoholosticha in the family Pseudokeronopsidae and support the distinctness of the new taxon as well as the monophyletic origin of the subfamily Nothoholostichinae.

Holocene temperature trends in the extratropical Northern Hemisphere based on inter‐model comparisons - Yurui Zhang; Hans Renssen; Heikki Seppä; Paul J. Valdes (Journal of Quaternary Science, 2018)
Large uncertainties exist in Holocene climate estimates, especially for the early Holocene when large‐scale reorganization occurred in the climate system. To improve our understanding of these uncertainties, we compare four Holocene simulations performed with the LOVECLIM, CCSM3, HadCM3 and FAMOUS climate models. The simulations are generally consistent for the large‐scale Northern Hemisphere extratropics, while the multi‐simulation consistencies are heterogeneous on the sub‐continental scale. Consistently simulated temperature trends are found in Greenland, northern Canada, north‐eastern and north‐western Europe, and central‐west Siberia. These Holocene temperatures show a pattern of an early Holocene warming, mid‐Holocene warmth and gradual decrease towards the pre‐industrial in winter, and the extent of early Holocene warming varies spatially, with 9 °C warming in northern Canada compared with 3 °C warming in central‐west Siberia. In contrast, mismatched temperatures are detected: in Alaska, the warm early Holocene winter in LOVECLIM primarily results from strongly enhanced southerly winds induced by the ice sheets; in eastern Siberia, the intense early‐Holocene summer warmth anomaly in CCSM3 is caused by large negative albedo anomalies due to overestimated snow cover at 0 ka; in the Arctic, cool winter conditons in FAMOUS can be attributed to extensive sea ice coverage probably due to simplified sea ice representations. Thus, the Holocene temperature trends in these regions remain inconclusive.

Study on dealkalization and settling performance of red mud - Muxi Luo; Xuejiao Qi; Yurui Zhang; Yufei Ren; Jiacheng Tong; Zining Chen; Yiming Hou; Nuerxiate Yeerkebai; Hongtao Wang; Shijin Feng; Fengting Li (Environmental Science and Pollution Research, 2017)

Characterization of the cellulolytic bacteria communities along the gastrointestinal tract of Chinese Mongolian sheep by using PCR-DGGE and real-time PCR analysis - Yan Zeng; Dong Zeng; Yan Zhang; Xueqin Ni; Yurui Tang; Hui Zhu; Hesong Wang; Zhongqiong Yin; Kangcheng Pan; Bo Jing (World Journal of Microbiology and Biotechnology, 2015)

Characteristics of porosity and permeability layer of fossil Halimeda reef mineral rock of Miocene in the Xisha Islands and its genetic model - Hong Xu; Yurui Zhu; G. P. Eberli; Wei Luo; Xinwei Zhao; Ying Cai; Xinyu Liu; Guijing Yan; Bolin Zhang; Kai Wei; Ruyong Cui (Acta Oceanologica Sinica, 2015)

Biogenic carbonate formation and sedimentation in the Xisha Islands: evidences from living Halimeda - Hong Xu; Xinwei Zhao; G. P. Eberli; Xinyu Liu; Yurui Zhu; Ying Cai; Wei Luo; Guijing Yan; Bolin Zhang; Kai Wei; Jian Shi (Acta Oceanologica Sinica, 2015)

Bioherm petroleum reservoir types and features in main sedimentary basins of the South China Sea - Hong Xu; Jing Sun; Jing Liao; Gang Dong; Jinqing Liu; Hongying Song; Zhenfeng Wang; Zhipeng Sun; Qinghuan Jin; Li Zhang; Kai Wei; Yurui Zhu; et al. (Journal of Earth Science, 2012)